Diagnosis and Treatment of Spinal Syphilitic Gumma: A Case Report - Cui, Linyang; Xu, Zushan; Hou, Hongjun (Frontiers in Neurology, 2020)
Neurosyphilis is a rare sexually-transmitted disease caused by Treponema pallidum involving the central nervous system (CNS). Spinal syphilitic gumma is extremely rare; only a few cases of spinal syphilitic gumma have been reported in the previous literature and almost all of them are subjected to surgery. Here we report a 46-year-old man, who presented with 5-day bilateral lower-limb numbness and lower back pain. Magnetic resonance imaging (MRI) suggested a homogeneous peripheral enhancement, intramedullary nodule at the T7 level associated with extensive thoracic cord edema. Laboratory examination and MRI revealed a syphilitic gumma. After penicillin G was used, the symptoms vanished a month latter and his intramedullary nodule disappeared as a result of the imaging after 6-month.